Stress-strain characteristic of SFRC using recycled fibres - Tlemat, H.; Pilakoutas, Kypros; Neocleous, Costas (My University, 2006)
This paper presents work from a comprehensive study on the development of a flexural design framework for concrete reinforced with steel fibres that are recovered from used tyres. The experimental flexural behaviour of notched concrete prisms reinforced with these fibres is initially presented. For comparison purposes, prisms reinforced with industrially produced fibres are also considered. An attempt to adopt an existing RILEM design framework to derive appropriate tensile stress-strain blocks is made, but problems are identified with key parameters of the framework. The influence of crack propagation and location of neutral axis depth on the tensile stress distribution is examined. Following an analytical study, it is concluded that the uniaxial stress-strain model, proposed by RILEM overestimates the load-carrying capacity and should be modified by utilising more advanced analytical techniques. © RILEM 2006.
Keywords: Steel fibers; Fiber reinforced materials; Fiber-reinforced concrete